Persepsi Petani dalam Pelaksanaan Program Asuransi Usaha Tani Padi di Keluarahan AEK Kecamatan Rantau Utara Kabupaten Labuhan Batu - Suryani Rezeki Siregar; Marliyah Marliyah; Rahmi Syahriza (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The Success Jaya Farmers Group located in Aek Paing Village North Rantau District, Labuhan Batu Regency, with an area of agriculture reaches 46 HA with 124 farmers and groups Tani Sukses Jaya is the farmer group that follows the most AUTP program. The number of people who signed up because the harvest was a lot which failed due to flooding. Know the focus of the problem in this research area: 1) What is the Farmer's Perception in the Implementation of the Insurance Program Rice Farming Business Insurance (AUTP) in Aek Paing Village, Rantau District North of Labuhan Batu Regency? 2) How is the Insurance Program Implemented Rice Farming Business (AUTP) in Aek Paing Village, Rantau Utara District Labuhan Batu Regency? The purpose of this research is to find out Farmers Perceptions in the Implementation of Rice Farming Business Insurance (AUTP) and also to find out how the farmers respond in the implementation Rice Farming Business Insurance (AUTP). This study uses a qualitative method with the type of descriptive research. Data collection techniques using interviews, to several informants, observations and documentation. For The validity of the data, use the credibility test. The results of this study show that the Implementation of the Rice Farming Business Insurance Program (AUTP) in Aek Village Paing, North Rantau District, Labuhan Batu Regency, very helpful Farmers because it is useful to get compensation assistance, so farmers can continue the business again and can help ease the burden on farmers due to crop failure. Farmers' Perceptions in the Implementation of Rice Farming Insurance (AUTP) received a positive response because with the existence of Business Insurance This rice farmer can ease the burden on farmers facing damage losses land and crop failure